2020
DOI: 10.1186/s43046-020-00047-z
|View full text |Cite
|
Sign up to set email alerts
|

Significance of p53, p27, Ki-67, E-cadherin, and HER2 expression in upper urinary tract urothelial carcinoma

Abstract: Background The study investigated the expression and the clinicopathological significance of p53, p27, Ki-67, E-cadherin, and HER2 in upper urinary tract urothelial carcinomas (UTUC) from Tunisian patients. We performed a retrospective study of 66 UTUC. Main clinicopathological features were reported. The expression of p53, p27, Ki-67, E-cadherin, and HER2 was investigated by immunohistochemistry on whole tissue section. Results Expression of p53, Ki-67, p27, E-cadherin, and HERE2 was reported in 36.4%, 69.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…In addition to TP53, ANXA10 expression was associated with a low Ki-67 LI. As a marker of cellular proliferation, high Ki-67 LI has been observed in 53–88% of UTUCs [32-35]. Previously, the high Ki-67 LI was found more frequently in T2-T4 tumors compared with Tis-T1 tumors and was correlated with adverse clinicopathological features, poor survival, and high risk of disease progression [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to TP53, ANXA10 expression was associated with a low Ki-67 LI. As a marker of cellular proliferation, high Ki-67 LI has been observed in 53–88% of UTUCs [32-35]. Previously, the high Ki-67 LI was found more frequently in T2-T4 tumors compared with Tis-T1 tumors and was correlated with adverse clinicopathological features, poor survival, and high risk of disease progression [33].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 16 eligible studies were identified (Figure 1). [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The main characteristics of the included studies, which were all retrospective, are summarized in Table 1 and Table 2. Among 16 studies, a total of 2030 UTUC patients ranging from 20 to 732 patients per study were reported.…”
Section: Study Selection and Characteristicmentioning
confidence: 99%
“…15 ERBB2 mutations have also been found in some patients with refractory renal pelvis carcinoma. 16,17 Notably, bladder cancer patients with an ERBB2 mutation showed a favorable response to trastuzumab. 18,19 However, there are limited reports on the use of trastuzumab in renal pelvis carcinoma.…”
Section: Introductionmentioning
confidence: 99%